Comparison of medium to long-term outcomes of acute severe ulcerative colitis patients receiving accelerated and standard infliximab induction. Issue 6 (13th December 2019) - Gibson, David J; Doherty, Jayne; McNally, Mairead; Campion, John; Keegan, Denise; Keogh, Aine; Kennedy, Una; Byrne, Kathryn; Egan, Laurence J; McKiernan, Susan; MacCarthy, FInbar; Sengupta, Subhasish; et al.
Abstract : Introduction: Accelerated dose infliximab (IFX) induction is associated with reduced short-term colectomy rate in acute severe ulcerative colitis (ASUC). Data on medium/long-term outcomes of this strategy are limited. Aims: Evaluate medium/long-term outcomes in patients receiving IFX induction for ASUC, comparing accelerated dose (AD) and standard dose (SD) induction. Methods: Retrospective study of consecutive patients admitted with corticosteroid-refractory ASUC in four tertiary referral centres within INITIative IBD research network (www.initiativeibd.ie ). IFX rescue was given either as SD (weeks 0, 2, 6) or AD (<28 days) from January 2010 to September 2017. AD induction has been utilised in participating centres since 2014. Consequently SD patients were subdivided based on time period of IFX rescue: historical SD group (SD1 ) (2010–2013) and current SD group (SD2 ) (2014–2017). Primary endpoint was time to colectomy; secondary endpoint was time to IFX discontinuation if induction was complete. Results: 145 patients received rescue IFX (AD=58, SD 1 =32, SD 2 =55). Disease severity at induction was comparable between AD and SD1 groups; however, SD2 group had less severe disease: median C-reactive protein (CRP) 39, 44 and 20 mg/L for AD, SD1 and SD2 groups, respectively (p=0.026, Kruskal-Wallis); median CRP: albumin ratio was 1.4, 1.8 and 0.6 (p=0.016). Median follow-up for AD, SD1 and SD2 groups was 1.6 (IQR 1.1–3.1), 4.9 (IQR 2.6–5.5) and 1.5 (IQR 0.9–2.3) years. Time to colectomy was shorter in SD1 (log rank p=0.0013); no significant difference in time to colectomy was observed comparing AD and SD2 groups (log rank p=0.32). 123 patients (84%) completed IFX induction and received maintenance therapy. Time to IFX discontinuation was shorter in SD1 (log rank p=0.009). Conclusion: Time to colectomy is significantly prolonged with use of AD IFX in selected ASUC patients with more severe disease. Historical use of standard IFX induction for all ASUC patients is associated with inferior long-term outcomes.